2012
DOI: 10.1165/rcmb.2012-0026oc
|View full text |Cite
|
Sign up to set email alerts
|

Integrative Assessment of Chlorine-Induced Acute Lung Injury in Mice

Abstract: The genetic basis for the underlying individual susceptibility to chlorine-induced acute lung injury is unknown. To uncover the genetic basis and pathophysiological processes that could provide additional homeostatic capacities during lung injury, 40 inbred murine strains were exposed to chlorine, and haplotype association mapping was performed. The identified single-nucleotide polymorphism (SNP) associations were evaluated through transcriptomic and metabolomic profiling. Using > 10% allelic frequency and > 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 106 publications
0
20
0
Order By: Relevance
“…In a process that consumes 40% of a cell's energy, Na,K-ATPase maintains the sodium-potassium electrochemical gradient across the plasma membrane by exporting three Na 1 and importing two K 1 for each ATP hydrolyzed (77). In previous metabolomics analyses of acrolein-and chlorine-induced lung injury, we observed that the lung undergoes energetic stress and that resistant mice appear better able to use substrates for energy production (33,34). The Na,K-ATPase-generated electrochemical gradient is essential for edema fluid absorption from the alveolus (1, 3).…”
Section: Discussionmentioning
confidence: 72%
See 4 more Smart Citations
“…In a process that consumes 40% of a cell's energy, Na,K-ATPase maintains the sodium-potassium electrochemical gradient across the plasma membrane by exporting three Na 1 and importing two K 1 for each ATP hydrolyzed (77). In previous metabolomics analyses of acrolein-and chlorine-induced lung injury, we observed that the lung undergoes energetic stress and that resistant mice appear better able to use substrates for energy production (33,34). The Na,K-ATPase-generated electrochemical gradient is essential for edema fluid absorption from the alveolus (1, 3).…”
Section: Discussionmentioning
confidence: 72%
“…The G allele is the minor allele (15.3% allelic frequency) and could result in the gain of a putative DNA binding site for transcription factor 12. Expressed in the lung (64), transcription factor 12 can repress E-cadherin (cadherin 1, type 1, E-cadherin [epithelial]) (65) and may modulate SMAD signaling (66), which is often active during ALI by transforming growth factor (TGF)b1 (32,34).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations